Effective synergy between UMP and AKEPT in promoting leadership for a sustainable organisation - UMP, PNC (2019)
The Higher Education Leadership Academy (AKEPT) has intensified its engagement programme with all public universities in matters relating to leadership and governance that would support the sustainability of competency-based talent management.